Filial Therapy-based Family for Children Disabilities to Reduce the Family Stress in COVID-19 Pandemic - Setyawati, Dewi; Al Jihad, Much Nurkharistna; Alfiyanti, Dera; Armiyati, Yunie (University of Muhammadiyah Semarang, 2022)
Filial therapy is a psychoeducational intervention designed to improve parent-child relationships, reduce problematic behavior in children, and reduce parental stress by including parents as therapeutic agents. Parent access-group sessions are facilitated by therapists who teach adult skills based on play therapy techniques, which parents then implement with their children under the supervision of a facilitator. The objective of this research is to determine differences in family stress between those who do Filial Therapy and those who do not receive Filial Therapy. The method used in this study is a quasi-experimental approach with a non-equivalent pre-post-test approach with a control group. Identification of respondents according to the criteria, namely families with ABK and school-age children with special needs (7-12 years) at SLB Semarang. The instrument used was a questionnaire of Perceived Stress Scale. Before treatment, the average stress level in the control group was higher than that in the intervention group, 17.25 (Standard Deviation ± 5.01). The average stress level in the control and intervention groups before Filial therapy was carried out was relatively the same at 17.25 and 16.87. In contrast, after Filial therapy was performed in both groups, the stress level decreased by 15.62 and 10.00. The analysis using the independent t-test showed differences in the reduction in stress levels in the control and intervention groups before and after Filial therapy (p-value = 0.000). Conclusion: it can be concluded that filial therapy can significantly reduce the stress level of families with children's disabilities.